Characterization of Aspergillus niger Isolated from the International Space Station - Jillian Romsdahl (American Society for Microbiology, 2018)
ABSTRACT The initial characterization of the Aspergillus niger isolate JSC-093350089, collected from U.S. segment surfaces of the International Space Station (ISS), is reported, along with a comparison to the extensively studied strain ATCC 1015. Whole-genome sequencing of the ISS isolate enabled its phylogenetic placement within the A. niger/welwitschiae/lacticoffeatus clade and revealed that the genome of JSC-093350089 is within the observed genetic variance of other sequenced A. niger strains. The ISS isolate exhibited an increased rate of growth and pigment distribution compared to a terrestrial strain. Analysis of the isolate’s proteome revealed significant differences in the molecular phenotype of JSC-093350089, including increased abundance of proteins involved in the A. niger starvation response, oxidative stress resistance, cell wall modulation, and nutrient acquisition. Together, these data reveal the existence of a distinct strain of A. niger on board the ISS and provide insight into the characteristics of melanized fungal species inhabiting spacecraft environments. IMPORTANCE A thorough understanding of how fungi respond and adapt to the various stimuli encountered during spaceflight presents many economic benefits and is imperative for the health of crew. As A. niger is a predominant ISS isolate frequently detected in built environments, studies of A. niger strains inhabiting closed systems may reveal information fundamental to the success of long-duration space missions. This investigation provides valuable insights into the adaptive mechanisms of fungi in extreme environments as well as countermeasures to eradicate unfavorable microbes. Further, it enhances understanding of host-microbe interactions in closed systems, which can help NASA’s Human Research Program maintain a habitat healthy for crew during long-term manned space missions.